PENGARUH SUBTITUSI PUREE JAMBU BIJI MERAH TERHADAP TOTAL FENOL, KANDUNGAN GIZI DAN DAYA TERIMA JELLY DRINK DAUN KACAPIRING - Wulan Eka Putri (2021)
Gardenia leaves have high phenol levels which as antioxidants can reduce free radical compounds, especially in obesity. The purpose of this study was to analyze the effect of red guava puree substitution on total phenol, nutritional content and acceptability, and determine the selected formula. This research used Completely Randomized Design with two repetitions. Jelly drink formula with the percentage level of red guava puree substitution is F1 (10%), F2 (20%), and F3 (25%). Analysis of total phenol test and nutritional content using the Anova test with Duncan's test continued. Organoleptic test data analysis used the Kruskal-Wallis test with continued Mann-Whitney test. The results showed that the level of substitution of red guava puree had a significant effect on total phenol (p=0.01) and water content (p=0.018), but had no effect on ash, protein, fat and carbohydrate content (p>0.05). Organoleptic analysis showed that red guava puree substitution had a significant effect on the acceptability of the gardenia leaf jelly drink based on aroma, taste and texture parameters but had no effect on color parameters. The selected formula is jelly drink F3 which has 93.31% water content, 1.61% ash, 1.47% protein, 0.19% fat, 3.4% carbohydrate, and 48 ± 6.265 mg GAE/kg phenol.